Preablative Stimulated Thyroglobulin Levels Can Predict Malignant Potential and Therapeutic Responsiveness of Subcentimeter-Sized, 18F-fluorodeoxyglucose-Avid Cervical Lymph Nodes in Patients With Papillary Thyroid Cancer. (January 2016) - Kwon, Seong Young; Kim, Jahae; Jung, Se Hee; Chong, Ari; Song, Ho-Chun; Bom, Hee-Seung; Min, Jung-Joon
Abstract : Purpose: We investigated the potential value of TSH-stimulated serum thyroglobulin (sTg) to characterize subcentimeter-sized, 18 F-FDG avid cervical lymph nodes (LNs) on PET/CT and their responsiveness to 131 I ablation therapy (IAT) in patients with papillary thyroid cancer. Materials and Methods: We enrolled 49 patients who were undergoing total thyroidectomy and had incidentally detected FDG-avid LNs on PET/CT before IAT. According to the follow-up results, FDG-avid LNs were classified into 2 groups: those with metastatic LNs (group A) and those with benign LNs (group B). Differences in clinical and histopathologic variables at the time of IAT (e.g., age, sex, pT stage, pN stage, LN location, sTg level, TSH level, maxSUV, and size of each FDG-avid LN) were compared between groups, retrospectively. In addition, responsiveness to IAT was assessed by the intensity of iodine uptake in posttherapeutic 131 I scans and by the reduction in LN size in follow-up studies. Results: Twenty of the 49 patients were classified in group A. By univariate analyses, sTg ( P = 0.001), maxSUV of FDG-avid LN ( P = 0.043), frequency of pT3-4 ( P = 0.032), pN1b ( P = 0.004), and FDG-avid LN located in mid to lower neck compartments ( P = 0.011) were all significantly higher in group A than in group B. Among the 5 variables, the level of sTg was the only significant parameter that could predict metastatic LNs in multivariate analyses (OR, 1.86; 95% CI, 1.14-3.06; P = 0.014). An ROC curve showed that sTg level of 6.0 ng/mL was the optimal cutoff for predicting metastatic LNs (sensitivity, 95.0%; specificity, 93.1%; area under the curve, 0.971; SE, 0.0223). Interestingly, these metastatic LNs showed no significant uptake of 131 I and no significant change of their size during follow-up. Conclusions: Subcentimeter-sized FDG-avid LNs with high levels of sTg (>6.0 ng/mL) were metastatic, non-iodine avid and had little effect in IAT. Therefore, appropriate follow-up strategies need to be undertaken in these patients.